2021
DOI: 10.1002/slct.202003948
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, Evaluation and Molecular Docking Studies of Novel Triazole Linked 1,4‐Dihydropyridine‐isatin Scaffolds as Potent Anticancer Agents

Abstract: A series of novel triazole linked isatin-dihydropyridine hybrids (N1-N15) have been synthesized and examined for their anti proliferative activity against human cancer cell lines viz. HeLa, Huh-7, PC-3, IMR-32 and MCF-7. All of the synthesized hybrids have shown moderate to potent cytotoxicity against all the tested cell lines except IMR-32. Compounds N1, N2 and N13 have displayed an enhanced inhibitory potency against Huh-7 cell line as compared to the standard drug, doxorubicin. Out of the three, N2 has show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…The IC 50 values of isatin-dehydroepiandrosterone conjugates (4a, 4d, and 4e) were reported as 28.19 ± 3.59, 13.90 ± 3.91, and 22.26 ± 6.21µM, respectively, against HuH-7 [44]. In another recent study on triazole-linked 1,4-dihydropyridine-isatin scaffolds (N1, N2, N13), the IC 50 values were evaluated as 13.66, 6.73, and 19.36 µM, respectively, for the same cell line [45]. The extract of Isatis indigotica leaves and indole alkaloids (Ih, Ij) were tested on the same cell line and the IC 50 values were reported as 58 µM [46] and 4.88 ± 0.78 and 6.60 ± 1.20 [47], respectively.…”
Section: Cytotoxicity Analysis By Cell Line Studiesmentioning
confidence: 99%
“…The IC 50 values of isatin-dehydroepiandrosterone conjugates (4a, 4d, and 4e) were reported as 28.19 ± 3.59, 13.90 ± 3.91, and 22.26 ± 6.21µM, respectively, against HuH-7 [44]. In another recent study on triazole-linked 1,4-dihydropyridine-isatin scaffolds (N1, N2, N13), the IC 50 values were evaluated as 13.66, 6.73, and 19.36 µM, respectively, for the same cell line [45]. The extract of Isatis indigotica leaves and indole alkaloids (Ih, Ij) were tested on the same cell line and the IC 50 values were reported as 58 µM [46] and 4.88 ± 0.78 and 6.60 ± 1.20 [47], respectively.…”
Section: Cytotoxicity Analysis By Cell Line Studiesmentioning
confidence: 99%
“…Indole derivatives (Figure 9), being diverse in nature, display a wide range of promising biological activities [77,78]. They have been shown effective against the novel coronavirus.…”
Section: Indole Analogmentioning
confidence: 99%
“…[10] However, off-lately, anticancer properties of 1,4-DHP derivatives have attracted a great deal of interest among medicinal chemists. [11][12][13][14][15] There are very few articles reported that discuss their anticancer activity. Dihydropyridines are also reported for their ability to reversing multidrug resistance on human carcinoma cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…Dihydropyridines are well known for their calcium channel blocking activity [10] . However, off‐lately, anticancer properties of 1,4‐DHP derivatives have attracted a great deal of interest among medicinal chemists [11–15] . There are very few articles reported that discuss their anticancer activity.…”
Section: Introductionmentioning
confidence: 99%